2023
DOI: 10.36740/wlek202303109
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Intermittent Fasting on Carbohydrate, Lipid and Ultrasonographic Parameters in Patients With Non-Alcoholic Fatty Liver Disease and Prediabetes

Abstract: The aim: To study intermittent fasting (IF) treatment in patients with non-alcoholic fatty liver disease (NAFLD) and prediabetes. Materials and methods: Patients with NAFLD (n=95) were examined. The patients were divided into 2 groups: Group 1 – NAFLD with obesity, Group 2 – NAFLD and prediabetes. All patients in both groups had Body mass index (BMI) within the 2nd degree of obesity range (30.0 kg/m2 to 34.5 kg/m2). Results: The effect of IF on anthropometric parameters, carbohydrate and lipid levels in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
0
0
Order By: Relevance
“…Human studies are less clear, however, depending on the groups studied. Recent meta-analyses of intermittent fasting studies in MASLD indicated that this intervention reduces body weight, liver enzymes, steatosis, and liver stiffness, particularly in overweight or obese individuals [32][33][34][35][36][37]. Another cross-sectional study reported that an eating window of <8 h was associated with a lower risk of MASLD [38].…”
Section: Introductionmentioning
confidence: 99%
“…Human studies are less clear, however, depending on the groups studied. Recent meta-analyses of intermittent fasting studies in MASLD indicated that this intervention reduces body weight, liver enzymes, steatosis, and liver stiffness, particularly in overweight or obese individuals [32][33][34][35][36][37]. Another cross-sectional study reported that an eating window of <8 h was associated with a lower risk of MASLD [38].…”
Section: Introductionmentioning
confidence: 99%